Pre Cal

posted by .

simplify the quotient: [x(5x+1)-3(x^2+1)]/ [(x-1)^2]

  • Pre Cal -

    [x(5x+1)-3(x^2+1)]/ [(x-1)^2]
    = (5x^2 + x - 3x^2 - 3)/(x - 1)^2
    = (2x^2 + x - 3)/(x-1)^2
    = (2x-3)(x+1)/(x-1)^2

    mmmh, looks like Much Ado About Nothing.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. PRE-CAL

  2. pre-cal

    can anyone please explain to me how to simplify this exponential expression?
  3. Pre-Cal

    Simplify e^3ln2-1
  4. Pre Cal

    simplify the expression 2sin^2 t + cos^2 t-2
  5. Pre Cal

    simplify the quotient: [(x+1)^3(4x-9)-(16x+9)(x+1)^2]/[(x-6)(x+1)^3]
  6. Pre-calculus

    The problem is Find the difference quotient and simplify your answer F(x)=5x - x^2, F(5+h) - F(5) over h ^2 this means power of two
  7. pre cal

    (y^2)^-4y^8 simplify
  8. Pre-Cal

    For given functions f and g find formulas for a)f o g and b)g o f. Simplify results as much as possible. f(t)= t-3/t+6 , g(t)= 1/(x+6)^2
  9. pre cal

    What would be the difference quotient,f(x+h)-f(x)/h , for the given function?
  10. Pre-Cal

    Confirm that f and g are inverses by showing that f(g(x)) = x and g(f(x)) = x. f(x) = (x-7)/(x+3) and g(x) = (-3x-7)/(x-1) I got to the point where f(g(x)) is plugged in but how would I simplify it?

More Similar Questions